2009
DOI: 10.1158/0008-5472.can-08-2345
|View full text |Cite
|
Sign up to set email alerts
|

l-Amino Acid Transporter-1 and Boronophenylalanine-Based Boron Neutron Capture Therapy of Human Brain Tumors

Abstract: The system L-amino acid transporter-1 (LAT-1) imports pboronophenylalanine (BPA) into cells and may play a major role in the effectiveness of BPA-based boron neutron capture therapy. The functional status of LAT-1 and its relationship to cell proliferation were simultaneously examined in the same section of human tumor material using a dual-labeling technique. The uptake of BPA (boron inductively coupled plasma mass spectrometry) was profiled in the presence of agonists and antagonists in fresh tumor explants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 30 publications
(33 reference statements)
3
87
0
Order By: Relevance
“…The microdistribution of boron compounds in peripheral tumors was studied using a SCC mouse model, with particular attention given to the quiescent cells, and this cell population was unable to accumulate BPA [9,10]. On the other hand, Detta and Cruickshank [13] stated that BPA-mediated BNCT might alter up to 70% of tumor cells expressing LAT-1, representing a three times higher proportion of tumor cells than their cell cycle status might suggest. In this case, LAT-1-negative cells would survive BNCT and be the cause of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microdistribution of boron compounds in peripheral tumors was studied using a SCC mouse model, with particular attention given to the quiescent cells, and this cell population was unable to accumulate BPA [9,10]. On the other hand, Detta and Cruickshank [13] stated that BPA-mediated BNCT might alter up to 70% of tumor cells expressing LAT-1, representing a three times higher proportion of tumor cells than their cell cycle status might suggest. In this case, LAT-1-negative cells would survive BNCT and be the cause of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the selective accumulation of amino acids was made possible by specific uptake mechanisms involving the system L family of heterodimeric, sodium-independent, amino acid transporters located at the plasma membrane, in particular L-amino acid transported-1 (LAT-1) [11,12]. Quiescent cells and a lack of LAT-1 expression may be responsible for the failure of BPA-mediated BNCT [13].…”
Section: Introductionmentioning
confidence: 99%
“…BPA is expected to be incorporated into tumour cells by specific uptake mechanisms involving LAT-1 [3,4,21,22]. BSH is not actively incorporated into tumour cells, but enters cells by a concentration gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Each B 4 C particle was encapsulated in a graphitic layer. They were dissolved in phosphate-buffered saline (PBS) and a stock solution was made of B 4 C at a concentration of 1,000 ppm.…”
Section: Boron Compound and Bnct For Cultured Cellsmentioning
confidence: 99%
See 1 more Smart Citation